An Early Insight into Language Acquisition: A Case Study of a 4-Year-Old Child’s Speech - Risa Laurie Mawardi (Kayee: Jurnal Pendidikan dan Ilmu Sosial, 2025)
This case study explores the early stages of language acquisition in a four-year-old Indonesian child by analyzing her spontaneous speech through the lens of psycholinguistic theory. Drawing on naturalistic data derived from two audio recordings of child-adult interaction, this research investigates the child's phonological patterns, morphological constructions, and semantic expressions to assess her linguistic development. Employing a qualitative descriptive method and content analysis, the study identifies systematic phonological substitutions (e.g., /r/ to /l/), productive morphological forms (e.g., compound numerals and affixation), and emergent semantic structures involving narrative coherence, emotional expression, and abstract concepts such as time and causality. Findings indicate that the child demonstrates age-appropriate linguistic features that align with developmental norms. The study underscores the significance of contextual interaction in fostering language development and reinforces the value of naturalistic observation in capturing children's real-time cognitive-linguistic strategies. This research contributes to the broader field of language acquisition studies by presenting empirical evidence from a culturally specific context.